SPE/DOE Enhanced Oil Recovery Symposium 1990
DOI: 10.2118/20178-ms
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to Gridding of Miscible Flood Predictions Made With Upstream Differenced Simulators

Abstract: SPE Members Abstract This paper examines the sensitivity to gridding of first-contact miscible and three-component multicontact miscible condensing-gas drive predictions made with an upstream differenced simulator. These cross-section simulations are made for various reservoir descriptions and for models of increasing numbers of grid blocks. The largest models range from 5000 to 24,000 grid blocks. The paper examines gridding sensitivity when the coefficients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Dispersion will result in loss of miscibility, as it causes the composition route to enter into the two-phase region. Zick (1986), Stalkup (1987) and Stalkup et al (1990) and others also indicate that O. Alomair et al / Predicting CO 2 Minimum Miscibility Pressure (MMP) Using Alternating Conditional Expectation (ACE) Algorithm numerical simulation and 1D slim-tube simulation give excellent match to the experimental data. Simulation of a slim-tube is significantly cheaper and faster than running the actual experiments but the phase behaviour of the oil and gas must be well-described by an EOS for a reliable MMP estimation.…”
Section: Methodsmentioning
confidence: 94%
“…Dispersion will result in loss of miscibility, as it causes the composition route to enter into the two-phase region. Zick (1986), Stalkup (1987) and Stalkup et al (1990) and others also indicate that O. Alomair et al / Predicting CO 2 Minimum Miscibility Pressure (MMP) Using Alternating Conditional Expectation (ACE) Algorithm numerical simulation and 1D slim-tube simulation give excellent match to the experimental data. Simulation of a slim-tube is significantly cheaper and faster than running the actual experiments but the phase behaviour of the oil and gas must be well-described by an EOS for a reliable MMP estimation.…”
Section: Methodsmentioning
confidence: 94%
“…Stalkup [22] also observed that for homogeneous and stratified systems recoveries decrease continuously with finer grids. In another study, Stalkup et al [23] further investigated the sensitivity of various miscible displacements in heterogeneous crosssections. They observed that recoveries could both increase or decrease with grid refinement and they noted that the trend could be either monotonic or nonmonotonic [23].…”
Section: Numerical Dispersion In Compositional Gas Simulationsmentioning
confidence: 99%
“…In another study, Stalkup et al [23] further investigated the sensitivity of various miscible displacements in heterogeneous crosssections. They observed that recoveries could both increase or decrease with grid refinement and they noted that the trend could be either monotonic or nonmonotonic [23]. In a recent study, Solano et al [24] investigated the interplay between heterogeneity and grid refinement.…”
Section: Numerical Dispersion In Compositional Gas Simulationsmentioning
confidence: 99%
“…The field started production in 1986, and has as of July 2003 produced roughly 300 MSm 3 of the currently estimated reserves of 342 MSm 3 . In place reserves are around 582 MSm 3 .…”
Section: Introduction To the Gullfaks Fieldmentioning
confidence: 99%
“…In place reserves are around 582 MSm 3 . Figure 3 shows the development in reserves and production from 1986 to date.…”
Section: Introduction To the Gullfaks Fieldmentioning
confidence: 99%